Genetic testing for childhood cancer predisposition syndromes: Controversies and recommendations from the SIOPE Host Genome Working Group meeting 2022 - Jette J. Bakhuizen; Franck Bourdeaut; Karin A.W. Wadt; Christian P. Kratz; Marjolijn C.J. Jongmans; Nicolas Waespe (EJC Paediatric Oncology)
Background: Cancer Predisposition Syndromes (CPSs) have been identified in 7–15 % of children with cancer. The possibilities for germline genetic testing have increased in recent years, presenting new opportunities but also challenges. There is currently no consensus on germline genetic testing in children with cancer in diagnostic settings. Methods: The International Society of Pediatric Oncology Europe (SIOPE) Host Genome Working Group used a consensus development conference method to reach agreement on four key topics: Who do we test? Which genes do we test? What do we disclose? How do we evaluate the benefits of testing? Results: The Working Group members agreed that: (1) All children with cancer should undergo clinical screening for their risk of harboring a CPS. (2) Targeted genetic testing based on clinical indication is recommended. Comprehensive CPS gene panels with more than 100–150 genes for all children with cancer should preferably be evaluated within research settings. (3) Smaller actionable gene panels can be considered including genes supporting diagnosis or influencing treatment decisions. (4) Clear pre-test information and consenting processes that highlight potential outcomes and implications of germline genetic testing are imperative. (5) Consequences of genetic testing, treatment adaption, and tumor surveillance in children with CPSs, including economic impact and psychosocial factors, should be further explored. Conclusions: These consensus-based recommendations provide guidance on germline genetic testing in children with cancer. Regular review of these recommendations is essential. Collaboration and the use of data sharing platforms can further improve screening procedures and its impact on care.